Bioesthetic Restoration on Endodontically Treated Tooth with Subgingival Extension: An Exploration of the Gellar Model - Aryal, A; Maskey, B; Mathema, S; Raja, MW; Shrestha, S; Karki, R; Hona, S (Journal of Nepalese Prosthodontic Society, 2024)
This case report highlights laboratory technique for fabricating prostheses in endodontically treated teeth with subgingival defects. The Gellar Model, a modified die system, is designed to create physiological and harmonious tooth contours, which can significantly improve periodontal health. This technique allows for better emergence profiles, contacts, and contours in the final prosthesis. While the fabrication process is both effective and efficient, it is challenging in terms of technical complexity and practicality, as it requires long working hours and high precision. However, with the growth of the digital market in dentistry, the scope of CAD/CAM technology is expanding, promising to alleviate the labor-intensive aspects of traditional methods.